Acute intoxication cases admitted to the emergency department of a university hospital - Kaya, Ertugrul (World J Emerg Med, 2015)
BACKGROUND: This study aimed to describe the clinical and socio-demographic aspects of acute poisoning in 2010 in Duzce City, Northwest Anatolian Region of Turkey. METHODS: Acute poisoning was due to the intentional ingestion of drugs in young and adult people (≥16), who were treated at the Emergency Service of Duzce University Medical Hospital, Turkey from January 1, 2010 to December 31, 2010. In this retrospective and descriptive study, 95 patients were diagnosed with intoxications and 30 of them intentionally ingested drugs to commit suicide. Records of the patients diagnosed with intoxication were obtained from the Clinical Archive of the hospital. Their diagnoses were established according to the International Statistical Classification of Diseases and Related Health Problems. Codes X60-X84 of this classification were used to classify self-infringed drug injuries and drug poisoning. RESULTS: In this series, 35 (36.8%) patients were male and 60 patients (63.2%) female. The male/female ratio was 1.0/1.7. The mean age of the patients was 33.1±14.2 years; 17 (17.9%) patients were below 20 years old and 9 (9.5%) were older than 50 years. Of these patients, 29 (30.5%) were single, 7 (7.4%) divorced or separated, and 59 (62.1%) married. Their mean time for admission to the emergency service after the incident was 208±180 (15–660) minutes. The mean time for admission to the emergency service for patients with food intoxication after the incident was 142±160 minutes, for those with drug intoxication 173±161 minutes, for those with carbon monoxide (CO) intoxication 315±209 minutes, and for those with undefined intoxication 289±166 minutes (P=0.005). Most of the intoxication cases occurred in winter (41.1%, 39 of 95 patients). Admissions to the emergency service were most common in December and April (21 and 16 of 95 patients, respectively). Sixty-five (68.4%) cases were involved in non-deliberate poisoning, whereas 30 (31.6%) were involved in deliberate poisoning. Twenty-six of the 95 patients with acute poisonings had mortality risk at admission, however only one died from CO intoxication in the emergency service (1.1%). Suicide attempts were more common in females than in males (21 of 30 patients, 70%, P<0.05). CONCLUSION: In Duzce City of Turkey, most intoxication cases occurred in winter, especially in December. They had non-deliberate poisoning, but deliberate poisoning in suicide attempts was more common in females than in males.